2010
DOI: 10.1021/ja109295x
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of the Efficient Nanoparticle Mediated Electron Transfer across a Self-Assembled Monolayer

Abstract: Recent advances in bioelectrochemistry came from the elaboration of conducting electrodes modified by an organic layer onto which nanoparticles are adsorbed. Self-assembled monolayers on noble-metal electrodes are known to hinder the electrochemical kinetics of fast-transfer redox systems. Surprisingly, fast kinetics are recovered when metal nanoparticles are deposited on top of the monolayer. We show that this surprising behavior can be fully accounted for when realizing that electron transfer from metal to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
219
1
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(255 citation statements)
references
References 17 publications
19
219
1
10
Order By: Relevance
“…In fact studies by us [2] and Fermin and co-workers [3] have shown that for self-assembled monolayers ranging in length between 3 and 11 carbons, the rate of electron transfer appears to be independent of the thickness of the otherwise insulating organic layer. This, somewhat unexpected observation, was very recently explained theoretically by Chazalviel and Allongue [4]. The explanation was that in the presence of the nanoparticles on top of the organic layer, the much higher density of states provided by the nanoparticle, relative to the density of states when the nanoparticles are absent, meant the exchange current density across the organic layer was many orders of magnitude higher than when the nanoparticles were absent.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In fact studies by us [2] and Fermin and co-workers [3] have shown that for self-assembled monolayers ranging in length between 3 and 11 carbons, the rate of electron transfer appears to be independent of the thickness of the otherwise insulating organic layer. This, somewhat unexpected observation, was very recently explained theoretically by Chazalviel and Allongue [4]. The explanation was that in the presence of the nanoparticles on top of the organic layer, the much higher density of states provided by the nanoparticle, relative to the density of states when the nanoparticles are absent, meant the exchange current density across the organic layer was many orders of magnitude higher than when the nanoparticles were absent.…”
Section: Introductionmentioning
confidence: 70%
“…AuNPs were synthesized using a 1 mM solution of HAuCl 4 in MilliQ water that was boiled prior to adding tri-sodium citrate with constant stirring. A colour change started to occur 10 s after the addition of citrate solution according to the method of Frens [14].…”
Section: Preparation Of Ito-organic Layer-aunps Constructsmentioning
confidence: 99%
“…This implies that the resistance of each BPT molecule is far below the quantum conductance, as previously suggested 17 . However this disagrees with [19][20][21][22].…”
mentioning
confidence: 77%
“…In addition to direct electrical connection between the buried AuNPs and HOPG, [26] this behavior may be due to fast ET between the electrode and metal NPs across an insulating film. [29] Even higher spatial resolution can be attained by using a smaller SECM tip. A constant height image of a 10 nm AuNP in Figure 4 a was obtained with a 3 nm-radius polished Pt tip.…”
Section: Np (Symbols Inmentioning
confidence: 99%